Larangan Bercadar di Perguruan Tinggi Perspektif Sadd al-Dzarî`ah - Andiko, Toha (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2018)
Abstract: The Prohabitions on Wearing Niqab (Face Covers for Mulism Women) in Higher Education Perspectives of Sadd al-dzarî`ah. Wearing niqab for women in colleges has recently become a polemic. This happened after two Islamic universities in Indonesia made a policy of prohibition for the academic community to wear the niqab on campus. Pros cons arise to address the policy of the rector II college. In the study of Jurisprudence, Hanafi, Maliki, and Shafi’i schools agree that women’s faces are not aurat (private parts of human’s body that cannot be exposed or should be covered according to Islam). Only the Hambali school of thought which says that the whole body of a woman, including the face, is aurat. Therefore, outside the prayers only Hambali schools that require covering the face for women by using niqab. While the other three schools of thought argue that wearing niqab is considered Sunnah (the way of the prophet), and can become mandatory if it is feared to cause slander. Since wearing niqab is categorized a khilafiah, the universities is entitled to establish a policy which prohibits its students to wear niqab: as long as this is believed and based on the strong and real reasons for its positive impact on the college and the student themselves. This action may be justified and appropriate under the sadd al-dzarî`ah proposition, as a preventive and anticipatory measure to prevent potential harm and damage that will result from wearing the veil on campus.